Performance Assessment of Android Antimalware Applications: An Experimental Approach - Lukman MOHAMMED; Victor O. WAZIRI; Ismaila IDRIS; Suleiman AHMAD (FUDMA Journal of Engineering and Technology, 2025)
The widespread use of Android phones has made the devices the primary target for malware authors. There are many commercial antimalware tools but they are not totally effective as android users still record high false positive rate. This research evaluates the performance of five common Android antimalware tools which include Kaspersky, BitDefender, Avira, Norton and McAfee against ten ransomware samples obtained from the AndMal2017 Android dataset. The experiment was conducted using Android Studio Emulator where each of the antimalware tool was tested to ascertain the detection rate, scan time and memory usage. Experimental results indicate that BitDefender achieved the highest detection accuracy of 90% with lowest scan time of 16.2 seconds and memory usage of 146.2MB. By providing quantitative benchmarks and an emulator-based testing framework, this research contributes practical insights for both academic and industry stakeholders in mobile cybersecurity.
Keywords: Malware, Android, Ransomware, Antimalware, detection.